A 33kV distribution network feeder reconfiguration by Using REPSO for voltage profile improvement - Sulaima, Mohamad Fani; Othman, Siti Noratika; Jali, Mohd Hafiz; Jamri , Mohd Saifuzam; Mohd Nasir, Mohamad Na'im; Bohari, Zul Hasrizal (Research India Publication, 2014)
The complexity of modern power system has contributed to the high power losses and over load in the distribution network. Due to that reason, Feeder Reconfiguration (FR) is required to identify the best topology network in order to fulfill the power demand with reduced power losses while stabilizing the magnitude of voltage. This paper addresses a new optimization method which is called as Rank Evolutionary Particle Swarm Optimization (REPSO). It has been produced by a hybridization of the conventional Particle Swarm Optimization (PSO) and the traditional Evolutionary Programming (EP) algorithm. The main objective of this paper is to improve the voltage profile while solves the overload problem by reducing the power losses respectively. The proposed method has been implemented and the real power losses in the 33kVdistribution system has been investigated and analyzed accordingly. The results are compared to the conventional Genetic Algorithm (GA), EP and PSO techniques and it is hoped to help the power system engineer in securing the network in the future.